Peningkatan Perkembangan Kognitif Anak Melalui Model Pembelajaran Teams Games Tournament dengan Media Balok - Muflichah Muflichah; Izatul Muwakidah (PG-PAUD Trunojoyo, 2018)
The purpose of this research was to determine the improve cognitive development through cooperative learning methods type Teams Games Tournament (TGT) with beam media and geometric shapes of group A children at Pertiwi IV Kindergarten Lamongan. The research design used adopted a spiral model from the opinion of Kemmis and Mc. Taggart consist of four phase, planning, implementation, observation, and reflection. This research consists of two cycles, each cycle consisting of 3 meetings / actions. Data analysis uses quantitative and qualitative data. Quantitative data analysis with descriptive statistics is to compare the results obtained from the first cycle and the second cycle. While the analysis of qualitative data by analyzing data from the results of field notes and interviews during the research with the steps of data reduction, data display and data verification. The results showed an increase in cognitive development in the ability to classify colors and geometric shapes through the TGT learning model with beam media, it can be proved that the average score of pre-cycle cognitive development scores was 34.38%. Then experienced an increase in the first cycle of 14.76% to 49.14%. Furthermore, from cycle I to cycle II cognitive development of children increased by 2.93% from 49.14% to 52.07%. So that the total increase in children's cognitive development starts from the pre-cycle, the first cycle to the second cycle is 34.38% which is 49.14% to 52.07%.